THE OPTIMUM PRODUCTION TIME OF LIPASE FROM ENDOPHYTIC BACTERIA LEAVES OF Macaranga hullettii King ex Hook.f. - Marliani, Nelly; Astuti, Winni; Kartika, Rudi (Jurusan Kimia FMIPA UNMUL, 2019)
Endophyte bacteria isolate from the leaves of Macaranga hullettii King ex Hook.f. has potential to producer lipase. In the study was conducted to filter lipase producing endophyte bacteria from Macaranga hullettii King ex Hook.f. and determine the optimum production time. The results of screening endophyte bacteria showed 6 isolates of endophyte bacteria that had the potential to produce lipase and 1 isolate was chosen which is number 5 to determine the optimum production time. The optimum production time of lipase from Macaranga hullettii King ex Hook.f. leaves for 72 hours with activity that is 2.92 U/mL.